PEMILIHAN PRIORITAS STRATEGI PEMASARAN COKLAT OLAHAN BERDASARKAN METODE ANALYTICAL HIERARCHY PROCESS (Studi Kasus di Perusahaan Magic Chocolate, Kabupaten Gianyar, Provinsi Bali) - FITRIA RETNONINGSIH; IGA OKA SURYAWARDANI; NYOMAN PARINING (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2016)
Abstract Analytical Hierarchy Process (AHP) Appliance on Choosing of Marketing Strategy Priority at Processed Chocolate (Case Study in Magic Chocolate, District Gianyar, Province Bali). Magic Chocolate is one of the home industries of processing cocoa in Bali with a venture business making chocolate as one of the refined products and seeks to grow its business through the marketing strategies appropriate. The purpose of this study was to determine the priority in the marketing strategy for the Magic Chocolate. Data collected by interviews and questionnaires. Data analysis methods that used in this research is using Analytical Hierarchy Process (AHP) with computer program Expert Choice. The study concluded that the priorities of business marketing strategy for the Magic Chocolate, first is the raw material (0,214), and then is the processing technology (0,188) and the third is a variety of products and packaging (0,183). The priority criteria of business marketing strategy obtained by the competitive prices (0,313), followed by an increase in demand (0,293), employment and improve household incomes (0,203), quality of products (0,191). Keywords : marketing strategy, Analytical Hierarchy Process, Magic Chocolate.